Fraksi Heksan dan Fraksi Metanol ekstrak biji Pepaya Muda dapat menghambat Spermatid Mencit Jantan (Mus musculus) - Komang Satriyasa, Bagus (Lembaga Penelitian Universitas YARSI, 2008)
Hexane fraction of unripe papaya seed extract contains glycosides, alkaloid and triterpenoids, which is assumed to have an anti fertility effect, so it can be used as a male contraception, although the mechanism of action is not yet clear. Research is conducted at Animal Laboratory Unit, Department of Pharmacology Faculty of Medicine University of Udayana, and Laboratorium Patologi Balai Penyidikan dan Pengujian Veterian (BPPV) Wilayah VI Denpasar Direktorat Jenderal Peternakan, Departemen Pertanian. This study used the pre-test and posttest control group design, using 30 male mice of balb C strain, aged 12 weeks, weight 20-22 gram, subsequently grouped by random into 3 groups each consisting of 10 male mice. One control group (P0 = control group) was given double distilled water, and two treatment groups (P1 = treatment group) was given fraction of the hexane extract of young Carica papaya seed 20 mg/20gram/day, (P2 = treatment group) was given fraction of the methanol extract of young Carica papaya seed 20 mg/20 gram/day. After 36 days of treatment, evaluation of the testis, of the male mice was conducted. Data were analysed by normality test of Kolmogorov Smirnov Goodness of Fit, homogeneity test, and Anova test. This study showed that spermatic cells decreased significantly (p < 0,01). It was concluded that hexane fraction and methanol fraction of unripe carica papaya seeds extract could decrease spermatic cells of male mice (mus musculus).